2020
DOI: 10.3390/cancers12092542
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin Signaling in Medulloblastoma

Abstract: Neurotrophins are a family of secreted proteins that act by binding to tropomyosin receptor kinase (Trk) or p75NTR receptors to regulate nervous system development and plasticity. Increasing evidence indicates that neurotrophins and their receptors in cancer cells play a role in tumor growth and resistance to treatment. In this review, we summarize evidence indicating that neurotrophin signaling influences medulloblastoma (MB), the most common type of malignant brain cancer afflicting children. We discuss the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 139 publications
(208 reference statements)
0
18
1
Order By: Relevance
“…Collectively, it can be deduced that NT5C2 plays a crucial role in the development and functional maintenance of neurosystem. Up to our knowledge, the NGF/TrkA signaling could participate in the process of cell survival, proliferation, and migration through at least three pathways, namely, RAS/RAF/MEK/ERK, PI3K/Akt, and PLC/PCK ( Thomaz et al, 2020 ; Esteban-Villarrubia et al, 2020 ). Through in silico analysis, we found that there were multiple binding sites of transcriptional factors such as STAT1β, ELK1, and NF-κB at the upstream promoter region of NT5C2 gene ( Supplementary Material 1 ), and all these factors are associated with at least one of the above pathways (27).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, it can be deduced that NT5C2 plays a crucial role in the development and functional maintenance of neurosystem. Up to our knowledge, the NGF/TrkA signaling could participate in the process of cell survival, proliferation, and migration through at least three pathways, namely, RAS/RAF/MEK/ERK, PI3K/Akt, and PLC/PCK ( Thomaz et al, 2020 ; Esteban-Villarrubia et al, 2020 ). Through in silico analysis, we found that there were multiple binding sites of transcriptional factors such as STAT1β, ELK1, and NF-κB at the upstream promoter region of NT5C2 gene ( Supplementary Material 1 ), and all these factors are associated with at least one of the above pathways (27).…”
Section: Discussionmentioning
confidence: 99%
“…The Notch, Wnt/β-catenin, and Hedgehog signaling pathways are additional conserved pathways that play important roles in NSC regulation throughout typical brain development and that also appear to have a role in medulloblastoma CSC maintenance and represent possible therapeutic targets (Figure 3). There are likely to be other pathways in normal neural development whose relationship with CSCs should be studied, such as neurotrophin signaling [52].…”
Section: Relationship Between Brain Tumor Cancer Stem Cells and Neural Stem Cellsmentioning
confidence: 99%
“…Although multimodal treatments with surgery radiotherapy and chemotherapy has improved cure rates, about one-third of patients relapse, and survivors experience long-lasting neurological, cognitive, and endocrinological sequelae. Thus, the development of molecularly targeted therapies is urgently needed [55][56][57][58].…”
Section: G9a and Medulloblastomamentioning
confidence: 99%